Analysis of factors self-harm behaviour among adolescents undergoing drug rehabilitation in Indonesia - Wardani, Ice Yulia; Nasution, Riska Amalya; Panjaitan, Ria Utami; Suratmini, Dwi; Rusiana, Elfira (Jurnal Ners, 2024)
Introduction:  The study aimed to analyse the factors associated with self-harm behaviour in adolescents in drug rehabilitation. Methods: This study used a descriptive-correlative design with a cross-sectional approach. The sample in this study was 241 adolescents who were in drug rehabilitation using the purposive sampling technique. This research was conducted in the Lido Centre for the Rehabilitation of the National Narcotics Agency, the Lampung Centre for Rehabilitation of the National Narcotics Agency, the Cipinang Besar Utara Narcotics Penitentiary, the Special Prison for Children of Jakarta, Lampung Narcotics Penitentiary, and the Al Islamy Foundation. This study used five questionnaires, namely the Internalized Stigma of Mental Illness, Self-Identity Questionnaire, UCLA Loneliness Scale Version 3, and the Deliberate Self-Harm Inventory. This study was analysed using a logistic regression test. Results: The results of the logistic regression analysis showed that, from several factors related to self-harm, namely loneliness, self-identity, and stigma, two factors that are most related to self-harm behaviour are self-identity and stigma, with a p-value of 0.000 (p<0.05). Conclusions: Self-harm behaviour can occur due to factors such as self-identity and stigma. This research can be a basis for providing nursing interventions to adolescents undergoing drug rehabilitation. Appropriate nursing interventions can help adolescents undergoing drug rehabilitation control the self-harm behaviour they want to engage in. Researchers recommend the importance of interventions aimed at strengthening self-identity and reducing stigma in efforts to prevent and treat self-harm behaviour. Additionally, future research is recommended to consider other variables that may also contribute to this behaviour.